2004
DOI: 10.1097/01.alc.0000121805.12350.ca
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heavy Drinking, Binge Drinking, and Family History of Alcoholism on Regional Brain Metabolites

Abstract: Community-dwelling HD who are not in alcoholism treatment have brain metabolite changes that are associated with lower brain function and are likely of behavioral significance. Age, FH, and binge drinking modulate brain metabolite abnormalities. Metabolite changes in active HD are less pronounced and present with a different spatial and metabolite pattern than reported in abstinent alcoholics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
3
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(147 citation statements)
references
References 66 publications
7
130
3
4
Order By: Relevance
“…Schizophrenia-MRS is capable of detecting both endogenous compounds in the brain as well as consumed or administered drugs ranging from anti-cancer agents (Port and Wolf, 2003), to alcohol ingested in excess (Danielsen and Ross, 1999) to anti-epileptic medications (e.g., valproic acid) administered in therapeutic doses (Bluml et al, 2002). Chronic alcoholism is accompanied by loss of NAA (Jagannathan et al, 1996;Meyerhoff et al, 2004) which in some studies is reported to recover after prolonged abstinence (Parks et al, 2002).…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 99%
“…Schizophrenia-MRS is capable of detecting both endogenous compounds in the brain as well as consumed or administered drugs ranging from anti-cancer agents (Port and Wolf, 2003), to alcohol ingested in excess (Danielsen and Ross, 1999) to anti-epileptic medications (e.g., valproic acid) administered in therapeutic doses (Bluml et al, 2002). Chronic alcoholism is accompanied by loss of NAA (Jagannathan et al, 1996;Meyerhoff et al, 2004) which in some studies is reported to recover after prolonged abstinence (Parks et al, 2002).…”
Section: Magnetic Resonance Spectroscopy and Imaging Of Naamentioning
confidence: 99%
“…Regional gray-matter, white-matter, and cerebrospinal-fl uid volumetry was performed using automated probabilistic segmentation, combined with automated atlas-based region labeling of the four lobes, cerebellum, and subcortical structures (Cardenas et al, 2005;Meyerhoff et al, 2004). Values obtained were normalized to intracranial volume for each participant.…”
Section: Magnetic Resonance Acquisition and Analysesmentioning
confidence: 99%
“…A number of these MRS studies, however, used metabolite ratios rather than absolute concentrations, typically relative to creatine (Cr), to quantify target metabolites, assuming that Cr is robust to CNS aging or insult and therefore remains stable. Indeed, several MRS studies report lack of significant deficits in uncomplicated alcoholics when regional measures of NAA were expressed as a function of the amount of underlying tissue (Mason et al, 2006;Meyerhoff et al, 2004;O'Neill et al, 2001;Pfefferbaum et al, 2005;Schweinsburg et al, 2000). In the Pfefferbaum et al study (2005), where NAA was expressed as a ratio of Cr, an apparent NAA deficit was present, but, it was as much attributable to a lower NAA peak as it was to a higher Cr peak in the alcoholics than controls.…”
Section: Introductionmentioning
confidence: 99%